Excavations at Stanground South, Peterborough : prehistoric, Roman and post-medieval settlement along the margins of the Fens - Boismier, W. A. (Archaeopress Archaeology, 2021)
This volume is a report of archaeological excavations at Stanground South undertaken by MOLA between September 2007 and November 2009 on behalf of Persimmon Homes (East Midlands) Ltd and in accordance with a programme of works overseen by CgMs Heritage. The work involved five areas of set-piece excavation and a series of strip map and record areas.